ASUHAN KEBIDANAN PADA Ny.H MASA KEHAMILAN TRIMESTER III, PERSALINAN, NIFAS, NEONATUS DAN KELUARGA BERENCANA DI PUSKESMAS MAOS: MIDWIFE CARE ON Mrs. H TRIMESTER III PREGNANCY, LABOR, PARTNERSHIP, NEONATUS AND FAMILY PLANNING AT MAOS PUSKESMAS - Risnawati Risnawati; Septi Tri Aksari; Yuli Sya’baniah; Ellyzabeth Sukmawati (Jurnal Ilmiah Kedokteran dan Kesehatan, 2022)
Every single woman will pass a pregnancy process, maternity and childbirth, it‘s a Physiological process. During the process there might be a health problem who can increase the pain even death for a mother and the baby. therefore, solutions are needed to prevent nor solving the problem, One of them Continuity of Care. The purpose of this research is provide comprehensive care from the period of pregnancy to contraception.Writing this Final Project Report in the form of case studies who uses Varney's 7-step midwifery management approach and documented in SOAP form. The sample used is 1 sample, namely Mrs.H at Puskesmas Maos. The results of this study obtained a diagnosis of Mrs H age 24 years old G2P1A0 gestational age 42 weeks physiological , on February 22, 2022, at 13.30 o‘clock, obtained complaints of regular heartburn spreading from the lower abdomen to the waist. on February 22, at 16.30 o‘clock the baby is born normally. In the care of newborns and neonatal visits were not a problem. On post partum and during home visits there are no problems, Mother has chosen to be an acceptor birth control pill for 3 month. The research results can be concluded there are no gaps between theories and practice on the application of midwifery care, in the upbringing process and Physiological changes. Every individual has uniqueness so that the care provided is also adapted to the patient's condition.